1998
DOI: 10.1002/(sici)1521-396x(199806)167:2<313::aid-pssa313>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Review of Trace Element Effects on High-Temperature Fracture of Fe- and Ni-Base Alloys

Abstract: Trace elements can have harmful or beneficial effects on elevated‐temperature mechanical properties. In iron and low‐alloy steels, S at high concentrations forms sulfides which are potent nucleation sites for intergranular creep cavities. As a result, ductility decreases and fracture becomes increasingly intergranular with increasing S concentration. Oxides and nitrides nucleate cavities only in the presence of segregated S; by themselves they are relatively benign. The harmful effects of S can be ameliorated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Therefore, the intrinsic cohesion of GB in high B doped alloy 2 is expected to be much crucial. As has been widely accepted, B segregation at GBs can increase the GB cohesion, tie up vacancies and reduce GB diffusion reaction, and thus prevents a premature formation of cavities and micro-cracks at the GBs 13 – 15. In the case of cavities formed, it has been found that B has segregated on the nucleated cavity surface during creep test,16 which decreased the diffusivity along the cavity surface and suppressed creep cavitation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the intrinsic cohesion of GB in high B doped alloy 2 is expected to be much crucial. As has been widely accepted, B segregation at GBs can increase the GB cohesion, tie up vacancies and reduce GB diffusion reaction, and thus prevents a premature formation of cavities and micro-cracks at the GBs 13 – 15. In the case of cavities formed, it has been found that B has segregated on the nucleated cavity surface during creep test,16 which decreased the diffusivity along the cavity surface and suppressed creep cavitation.…”
Section: Discussionmentioning
confidence: 99%
“…Trace elements in a material can influence the intergranular creep cavity nucleation and growth processes critically because of their strong segregation tendencies to the grain boundary and nucleated cavity surface. [8,9,12] Holt and Wallace [13] classified the most common trace elements according to whether they have detrimental or beneficial effects on creep rupture strength. Among them, oxygen and sulfur can cause the most severe embrittlement during creep even at low levels.…”
Section: Introductionmentioning
confidence: 99%